Authorial Voice in Islamic College English Department Students’ Argumentative Writing - Afifi, Nur (JEELS (Journal of English Education and Linguistics Studies), 2014)
While considered elusive and abstract, authorial voice is paramount in English writing. Unfortunately, many of Indonesian EFL learners found it is highly challeging to show their voice in their writing. The importance of voice is even exaggerated in argumentative writing, since this kind of writing needs obvious stance of the writer. This study investigates the authorial voice students made in their argumentative writing. The purpose of this study is to gain the picture of students' writing ability especially in authorial voice to map the road in guiding the next writing classes. The object of the study is the argumentative writing made by English department students' at one Indonesian State College of Islamic Studies in their writing III course. Using Hyland's interactional model of voice (2008) the data analysis results the authorial presence in the essays is in position 2 at 0 ² 4 scale which means the reader feels somehow weak presence of the authorial voice in the essay. This result confirms the findings of some previous studies that EFL learners especially from 'interdependent' cultural background tend to find this authorial voice difficult in writing English essay.